Method and Theory in Religious Studies: Retrospect and Prognostications - Morny Joy (Temenos, 2007)
There is a distinct possibility that, in the twenty-first century, Religious Studies as a discipline could come into its own. Its multidisciplinary orientation, if handled with due critical awareness as to its own former grandiose ambitions and present entanglements, could provide insight into the various problems that beset contemporary existence. Religious Studies has been involved in a number of internal debates that have sapped its energies and prevented it from advancing theoretically in ways that would help it address these problems. In this article I survey some of the developments that have taken place in other disciplines that could be of benefit in helping Religious Studies take its place as a discipline that is relevant for the twenty-first century.